2023
DOI: 10.1111/polp.12529
|View full text |Cite
|
Sign up to set email alerts
|

Catching up withAI: Pushing toward a cohesive governance framework

Abstract: Artificial Intelligence (AI) contributes to public administration by augmenting public services, including managing big data and information technology. AI is currently utilized in e‐government services that contribute value to American citizens, including providing a personalized customer experience, such as linking individualized data and processing individual assistance requests. Furthermore, AI can take over redundant routine tasks such as digital information provisioning and delivering services. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 91 publications
1
6
0
1
Order By: Relevance
“…Veloso Meireles (2024) puts digital rights in perspective by examining debates in the Internet Governance Forum over the last two decades. The article is not only essential reading for scholars in the areas of digital democracy, cyber governance/regulation, and cyber security (see also Glen, 2021;Hellmeier, 2016;Robles & Mallinson, 2023;Zeng et al, 2017) and their history. It will also be of prime interest to anyone who has harbored reservations about the ability of intelligent algorithms to store personal information-thereby inducing increased consumption and other behaviors-and the huge surveillance and privacy implications of this.…”
Section: Summary Of Articles In the February 2024 Issue Of Politics A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Veloso Meireles (2024) puts digital rights in perspective by examining debates in the Internet Governance Forum over the last two decades. The article is not only essential reading for scholars in the areas of digital democracy, cyber governance/regulation, and cyber security (see also Glen, 2021;Hellmeier, 2016;Robles & Mallinson, 2023;Zeng et al, 2017) and their history. It will also be of prime interest to anyone who has harbored reservations about the ability of intelligent algorithms to store personal information-thereby inducing increased consumption and other behaviors-and the huge surveillance and privacy implications of this.…”
Section: Summary Of Articles In the February 2024 Issue Of Politics A...mentioning
confidence: 99%
“…关键词: 《政治与政策》杂志,P&P,编辑建议,假新闻,选举,粮食安全,互联网治理,性别,地缘 经济学,腐败,政策反馈,接受出版 欢迎阅读《政治与政策》(P&P)2024年第一期!本期将于二月出版,内容涵盖了广泛的政治学和比 较国际政策学术,包括假新闻和选举、粮食安全、互联网治理、关于性别的多种视角、地缘经济学、 腐败、政策等! 我们的第一篇文章直接指向近期的技术变革。Veloso Meireles(2024)通过分析过去二十年互联网 治理论坛中的辩论,提出了"正确看待数字权利"。这篇文章不仅是研究数字民主、网络治理/监管和 网络安全领域学者的必读书(see also Robles and Mallinson, 2023;Glen, 2021;Zeng, Stevens, and Chen, 2017;Hellmeier, 2016) Duit, Lim, and Sommerer, 2023;Tawiah, 2022)…”
Section: Pol Itics and Pol Icy Y Algunos Consejos De La Ed Itoraunclassified
“…While previous studies identified factors affecting AI adoption, little research explores strategies for effectively using AI to enhance overall OP (Dwivedi et al , 2021; Mikalef et al , 2023; Valle-Cruz and García-Contreras, 2023). Several studies have demonstrated that the use of AI in public administration has resulted in enhancements in the perceived value of public services (Robles and Mallinson, 2023), the decision-making processes (Gaozhao et al , 2023) and the allocation of resources (Mikalef et al , 2023). Consequently, these improvements have led to increased effectiveness, efficiency and convenience for citizens (Yigitcanlar et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…AI adoption has surged by 270% in the past four years, with a further tripling in the most recent year (Gerner, 2020). However, many organizations face challenges in effectively using AI solutions (Neumann et al , 2022; Robles and Mallinson, 2023). Consequently, it remains uncertain how government organizations can optimize their investment in AI by leveraging complementary resources and enhancing organizational performance (OP) (Mikalef et al , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In our first article, Robles and Mallinson (2022–23) use their outstanding systematic review to flag the inconsistent public policy that currently regulates artificial intelligence (AI) and to underline the need for a coherent, yet adaptable, AI governance model to guide policy and administration scholars and practitioners. In “Catching Up With AI: Pushing Toward a Cohesive Governance Framework,” Robles and Mallinson not only offer a comprehensive review of the extant research on the subject.…”
Section: Yearbook Review 2022–23 Issue Summarymentioning
confidence: 99%